An Ecological Momentary Assessment of Lapse Occurrences in Dieters. Issue 3 (22nd February 2014) - McKee, Heather C.; Ntoumanis, Nikos; Taylor, Ian M.
Abstract: Purpose: The aim of this study is to investigate the factors related to dietary lapse occurrence in a community sample of dieters. Methods: An ecological momentary assessment (EMA) methodology, via mobile phone-based diaries, was employed to record dietary lapse occurrences in a group of dieters ( N  = 80; Mage  = 41.21 ± 15.60 years; M BMI  = 30.78 ± 7.26) over 7 days. Results: Analyses indicated that lapses were positively associated with the strength of dietary temptation, presence of others, coping responses, and the environment (exposure to food cues) in which the dieters were in; lapses were more likely to occur in the evening and were negatively associated with the use of coping mechanisms. Additionally, lapse occurrence was found to mediate the relationships among the above predictors of lapse and the self-efficacy to resist future dietary temptations. Conclusions: Results provide an insight into the occurrence of lapses in dieters and have implications for interventions focusing on weight loss maintenance and relapse prevention.